EKSPLORASI DETERMINAN INTENSI PERGANTIAN DOSEN DI PERGURUAN TINGGI SWASTA MELALUI ANALISIS FAKTOR - Nafiudin, Nafiudin; Chairani, Ayu (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
Purpose – The purpose of this study is to find new criteria that influence the intention in and out of private lecturers in Banten Indonesia Methodology – This study used convenience strategies to obtain 102 samples. Online questionnaire dissemination is used to obtain primary data Findings – There are 30 criteria used to predict a lecturer's exit intention. 15 criteria that affect the intention to leave lecturers as a result of factor analysis, from 15 criteria grouped into three factors, namely, total rewards, organizational climate, and employer branding Originality – Originality produces new knowledge without repeating what has already been done by others